The Influence of Entrepreneurial Knowledge and Career Planning on the Work Readiness of Digital Business XI Students - Simanjuntak, Thomas Alpa Rich; Agusti, Ivo Selvia (Economic: Journal Economic and Business, 2025)
This study aims to analyze the influence of entrepreneurial knowledge and career planning on the work readiness of Grade XI Digital Business students at SMK Swasta Budi Agung Medan in the 2024/2025 academic year. The research employs a quantitative approach with an ex post facto design. The sample consisted of all 30 students from the Grade XI Digital Business class, selected using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The results reveal that: (1) entrepreneurial knowledge and career planning simultaneously have a positive and significant effect on work readiness (F-value = 21.592; sig = 0.000); (2) entrepreneurial knowledge has a significant partial effect on work readiness (t-value = 2.650; sig = 0.013); and (3) career planning also significantly influences work readiness (t-value = 2.235; sig = 0.034). The contribution of both independent variables to work readiness is 61.5%. These findings highlight the importance of entrepreneurial education and structured career planning in enhancing vocational students' preparedness for entering the workforce.